Perkembangan Busana Adat Ke Pura Umat Hindu Di Bali Dalam Era Globalisasi - Ni Luh Ketut Sukarniti (Jurnal Ilmiah Cakrawarti, 2018)
Along with the times and also the flow of globalization are brings the influence of changes in the environment on the people of Bali. This change can occur in various aspects of life such as equipment and supplies, livelihoods, social systems, language, arts, knowledge systems and religion or belief.The deterioration in the quality of the environment arises from various environmental problems, has made humans aware of the importance of environmental support for life in the universe. The environment cannot support an unlimited number of lives. Environmen- tal conservation must be maintained as it is. This means that the environment is undergo- ing a process of change.If you pay attention, there are very many indigenous cultures of the archipelago that have experienced a shift due to the flow of globalization, be it language culture, even a cultural shift in dress